(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Medicinal plants growing on the northern slope of the Kyrgyz Alatau Mountains are distinguished by their species diversity. There are species among them that are widely used in traditional medicine, as well as less popular ones due to their insufficient research and lack of coverage. Due to the proximity of settlements, medicinal plants are affected by anthropogenic impact. Overgrazing and uncontrolled harvesting of plant material damage the biodiversity of the area. The article provides a characterization of individual species of medicinal plants and their methods of using in folk medicine.